2007
DOI: 10.1002/art.22507
|View full text |Cite
|
Sign up to set email alerts
|

Country as the primary risk factor for renal amyloidosis in familial mediterranean fever

Abstract: Objective. Familial Mediterranean fever (FMF), the prototype of autoinflammatory disorders, is caused by recessive mutations in the MEFV gene. Some FMF patients develop renal amyloidosis, a potentially fatal condition. This complication has mainly been associated with the M694V mutation, although the different study designs, small numbers of patients, and/or evaluation of few or no covariables calls this association into question. The aim of this study was to examine the controversial issue of amyloidosis susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
141
0
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 243 publications
(155 citation statements)
references
References 23 publications
1
141
0
10
Order By: Relevance
“…Previous studies have shown that the risk of developing severe disease phenotype is higher in patients who are homozygous for M694V (10). It was observed that the homozygous state for M694V was a high risk factor for amiloidosis in Armenians, Israelis, and Arabs (11). In a meta-analysis that included 3505 Turkish patients, it was shown that 189 of 400 patients who developed amilosidosis were M694V homozygous (12).…”
Section: Familial Meditarenean Fevermentioning
confidence: 99%
“…Previous studies have shown that the risk of developing severe disease phenotype is higher in patients who are homozygous for M694V (10). It was observed that the homozygous state for M694V was a high risk factor for amiloidosis in Armenians, Israelis, and Arabs (11). In a meta-analysis that included 3505 Turkish patients, it was shown that 189 of 400 patients who developed amilosidosis were M694V homozygous (12).…”
Section: Familial Meditarenean Fevermentioning
confidence: 99%
“…FMF is an autoinflammatory disorder that occurs in the absence of autoantibodies or antigen-specific T cells. It is characterized by recurrent self-limited episodes of periodic fever and painful polyserositis, affecting mainly the peritoneum, pleura, and synovium (1,2). Why the attacks cease in the disease is as intriguing as why they start, and why amyloidosis develops in some patients is another intriguing question.…”
Section: To the Editormentioning
confidence: 99%
“…The drug should be used continuously (1), not intermittently as in the treatment of gout attacks. Colchicine inhibits neutrophil motility (chemotaxis; infiltration into the tissue) continuously, and prevents cellular accumulation and weakens serum amyloid formation in the inflamed regions.…”
Section: To the Editormentioning
confidence: 99%
“…FMF is an autosomal-recessive inherited inflammatory disease caused by mutations in the MEFV gene encoding a protein called pyrin (also known as marenostrin). A multicenter study published by Touitou et al [1] found an overall prevalence of AA amyloidosis in FMF patients of 11.4%. The incidence varied depending on the country of residence and M694V homozygosity.…”
Section: Introductionmentioning
confidence: 96%